Detection of the Antiseptic Resistance Gene among Pseudomonas aeruginosa Isolates - Ù†Ø¹Ù…Ø©, Ø§Ø®Ù„Ø§Øµ (Iraqi Journal of Science, 2021)
Pseudomonas aeruginosa is an opportunistic pathogen that causes a number of infections in immunocompromised patients. This organism appears to improve resistance to many antimicrobial agents and a high percentage of clinical isolates of P. aeruginosa exhibit multidrug resistance (MDR) phenotype . The purpose of this study is to screen the antibiotic susceptibility patterns and the prevalence of qacE delta1 gene among bacterial isolates. Accordingly, 145 samples were collected from different clinical sources from patients who admitted to different hospitals in Baghdad city in a period ranged 23/8/2018-1/1/2019. The isolates were diagnosed as P. aeruginosa based on routine bacteriological methods and confirmed by a molecular method using 16SrRNA gene. The antibiotic susceptibility test was performed to all identified isolates by Kirby-Bauer Disk Diffusion method using ten types of antibiotics. The results of antibiotics susceptibility test revealed high levels of resistance toward Piperacillin (72.22%), Trimethoprim (68%), Ceftazidime (68%), Colistin (40.28%), and Levofloxacin (33.33%). And , the minimum inhibitory concentration (MIC) of Cetrimide was tested using different concentrations (2.048 to 0.004Âµg/100Âµl) and the results showed that MIC values ranged between 2.048 and 0.016) Î¼g/100Î¼L, and the concentration of 0.256 Î¼g/100Î¼l was more frequent . Finally, the prevalence of qacE delta1 gene among bacterial isolates was detected in percentage 63.88% among bacterial isolates .